Cancer‐induced cardiac atrophy adversely affects myocardial redox state and mitochondrial oxidative characteristics. Issue 1 (7th August 2020) - Lee, David E.; Brown, Jacob L.; Rosa‐Caldwell, Megan E.; Perry, Richard A.; Brown, Lemuel A.; Haynie, Wesley S.; Washington, Tyrone A.; Wiggs, Michael P.; Rajaram, Narasimhan; Greene, Nicholas P.
Abstract: Background: Cachexia presents in 80% of advanced cancer patients; however, cardiac atrophy in cachectic patients receives little attention. This cardiomyopathy contributes to increased occurrence of adverse cardiac events compared with age‐matched population norms. Research on cardiac atrophy has focused on remodelling; however, alterations in metabolic properties may be a primary contributor. The purpose of the study is to determine how cancer‐induced cardiac atrophy alters mitochondrial turnover, mitochondrial mRNA translation machinery, and in vitro oxidative characteristics. Methods: Lewis lung carcinoma (LLC) tumours were implanted in C57BL6/J mice and grown for 28 days to induce cardiac atrophy. Endogenous metabolic species and markers of mitochondrial function were assessed. H9c2 cardiomyocytes were cultured in LLC‐conditioned media with (out) the antioxidant MitoTempo. Cells were analysed for reactive oxygen species (ROS), oxidative capacity, and hypoxic resistance. Results: LLC heart weights were 10% lower than controls. LLC hearts demonstrated 15% lower optical redox ratio [flavin adenine dinucleotide (FAD)/FAD + nicotinamide adenine dinucleotide hydrogen (NADH)] compared with phosphate‐buffered saline controls. When compared with phosphate‐buffered saline, LLC hearts showed 50% greater Cytochrome‐C oxidase subunit 4 (COX‐IV) and Voltage‐dependent anion channel (VDAC), attributed to 50% lower mitophagy markers. mt‐mRNA translation machinery was elevated similarly to markers of mitochondrial content. Mitochondrial DNA‐encoded Cytb was 30% lower in LLC hearts. ROS scavengers GPx‐3 and GPx‐7 were 50% lower in LLC hearts. Treatment of cardiomyocytes with LLC‐conditioned media resulted in higher ROS (25%), lower oxygen consumption rates (10% at basal and 75% at maximal), and greater susceptibility to hypoxia ( 25%), which was reversed by MitoTempo. Conclusions: These results substantiate metabolic cardiotoxic effects attributable to tumour‐associated factors and provide insight into interactions between mitochondrial mRNA translation, ROS mitigation, oxidative capacity, and hypoxia resistance.